Prevalence, Characterization, and Drug Resistance of Staphylococcus Aureus in Feces From Pediatric Patients in Guangzhou, China - Ai, Xiaolan; Gao, Fei; Yao, Shuwen; Liang, Bingshao; Mai, Jialiang; Xiong, Zhile; Chen, Xiantang; Liang, Zhuwei; Yang, Hongling; Ou, Zhiying; Gong, Sitang; Long, Yan; et al. (Frontiers in Medicine, 2020)
Background: Staphylococcus aureus (S. aureus) is a major pathogen of human infections. Its faecal carriage serves as a risk factor for nosocomial transmission and disease development. However, the rate of S. aureus faecal carriage among Chinese children has not yet been reported. Therefore, we sought to investigate the prevalence, characterization, and drug resistance of S. aureus isolated from paediatric patients’ faeces in Southern China. Methods: Fecal samples (2,059) from paediatric patients in three centers in Guangzhou were cultured. From which, 412 S. aureus isolates were identified via selective mediums and automated VITEK Mass Spectrometer analysis. Antibiotic susceptibility was determined and DNA sequencing of seven housekeeping genes were used for multi locus sequence typing analysis. Results: The faecal carriage rates were 20.0% for S. aureus and 4.5% for methicillin-resistant S. aureus (MRSA). Moreover, S. aureus faecal carriage was positively correlated with outpatient status and gastroenteritis diagnosis. Moreover, age-related patterns were observed with respect to prevalence of S. aureus. Besides, a total of 76 sequence types (STs) were identified, including 25 newly assigned STs and 28 clonal complexes (CCs). ST188, ST6 and ST15 were the most prevalent methicillin-sensitive S. aureus (MSSA) clones, while ST59 and ST45 were the major MRSA clones. S. aureus isolates also exhibited high rates of penicillin (84.2%), erythrocin (38.8%) and clindamycin (35.9%) resistance. Specifically, all ST30 and ST338 isolates were resistant to erythrocin and clindamycin, 61% of ST7 were resistant to tetracycline and 84% of ST45 exhibited resistance and intermediate resistance to rifampicin. Also, CC59 (ST338 and ST59) and CC45 exhibited different antibiotic resistance patterns. Conclusion: These results demonstrate the colonization dynamics and molecular epidemiology of S. aureus in child faeces in Southern China. Further, they suggest an urgent for strengthening the surveillance programmes in China, and provide important information for the prevention and treatment of S. aureus infection.